Cafe Variome: General‐Purpose Software for Making Genotype–Phenotype Data Discoverable in Restricted or Open Access Contexts. Issue 10 (25th August 2015) - Lancaster, Owen; Beck, Tim; Atlan, David; Swertz, Morris; Thangavelu, Dhiwagaran; Veal, Colin; Dalgleish, Raymond; Brookes, Anthony J
<x xml:space="preserve">Abstract</x> Data 'discovery' solutions enable users to quickly and accurately identify where useful data are located, thereby promoting collaboration around such datasets, and underpinning appropriate data sharing arrangements in restricted and open access contexts. Convenient, flexible, web‐based, data discovery software is therefore needed, and Cafe Variome (www.cafevariome.org) represents one such tool that enables single groups or networks to advertise and/or share data in an appropriately controlled manner.